2019
DOI: 10.1158/2326-6066.cir-19-0152
|View full text |Cite
|
Sign up to set email alerts
|

Trabectedin Reveals a Strategy of Immunomodulation in Chronic Lymphocytic Leukemia

Abstract: Chronic lymphocytic leukemia (CLL) is a B-cell neoplasia characterized by pro-tumor immune dysregulation involving non-malignant cells of the microenvironment, including T lymphocytes and tumor-associated myeloid cells. Although therapeutic agents have improved treatment options for CLL, many patients still fail to respond. Some patients also show immunosuppression. We have investigated trabectedin, a marine-derived compound with cytotoxic activity on macrophages in solid tumors. Here we demonstrate that trabe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 51 publications
(77 reference statements)
1
33
0
Order By: Relevance
“…One additional observation was the decrease in the cell surface levels of PD-L1, which might contribute to reinforce the immune surveillance action of the adaptive immune system against tumor cells [ 43 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…One additional observation was the decrease in the cell surface levels of PD-L1, which might contribute to reinforce the immune surveillance action of the adaptive immune system against tumor cells [ 43 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A preclinical study recently showed in a chronic lymphocytic leukemia mouse model that trabectedin induced leukemic cell death and depletion of the immuno-suppressive myeloid-derived suppressor cells and TAMs [102]. Anti-tumor activity by trabectedin, through effects on TAMs, has also been reported in pre-clinical models of skeletal metastatic prostate tumor, melanoma, and pancreatic tumor [103][104][105].…”
Section: Strategies To Deplete Tamsmentioning
confidence: 97%
“…In CLL, trabectedin has shown to induce cytotoxic effects in leukemic cells and concomitantly exerts immunomodulatory activity on several cell types of the microenvironment. It depletes myeloid-derived suppressor cells and tumor-associated macrophages and induces T cell response [ 71 ].…”
Section: Introductionmentioning
confidence: 99%